Blood-compatible poly (2-methoxyethyl acrylate) for the adhesion and proliferation of lung cancer cells toward the isolation and analysis of circulating tumor cells. (July 2016) - Hoshiba, Takashi; Nikaido, Mayo; Yagi, Satomi; Konno, Iku; Yoshihiro, Ayano; Tanaka, Masaru
Circulating tumor cells have received attention for their role in cancer diagnosis and the decision on which chemotherapeutic course to take. For these purposes, the isolation of circulating tumor cells has been important. Previously, we reported that non-blood cells can adhere on blood-compatible polymer substrates, such as poly(2-methoxyethyl acrylate) and poly(tetrahydrofurfuryl acrylate). In this study, we examined whether blood-compatible poly(2-methoxyethyl acrylate) and poly(tetrahydrofurfuryl acrylate) allow the adhesion and growth of A549 lung cancer cells for isolating circulating tumor cells by adhesion-mediated manner to diagnose metastatic cancer and to decide on the chemotherapeutic course. A549 cells can adhere on poly(2-methoxyethyl acrylate) and poly(tetrahydrofurfuryl acrylate) substrates via an integrin-dependent mechanism after 1 h of incubation, suggesting that blood-compatible poly(2-methoxyethyl acrylate) and poly(tetrahydrofurfuryl acrylate) substrates possess the ability to capture circulating tumor cells selectively from peripheral blood. After 1 day of culture, A549 cells started to spread on poly(2-methoxyethyl acrylate) and poly(tetrahydrofurfuryl acrylate) substrates. A549 can also grow on poly(2-methoxyethyl acrylate) and poly(tetrahydrofurfuryl acrylate) substrates. Additionally, the chemoresistance of A549 cells against 5-fluorouracil on poly(2-methoxyethyl acrylate) and poly(tetrahydrofurfuryl acrylate) substrates was similar to that on the conventional cell culture substrate, tissue culture polystyrene. These results indicate that circulating tumor cells can be cultured on poly(2-methoxyethyl acrylate) and poly(tetrahydrofurfuryl acrylate) substrates after they are isolated from peripheral blood, and poly(2-methoxyethyl acrylate) and poly(tetrahydrofurfuryl acrylate) substrates can be used as circulating tumor cell culture substrates for screening anti-cancer drugs. Therefore, poly(2-methoxyethyl acrylate) and poly(tetrahydrofurfuryl acrylate) substrates might be able to be applied to the development of a new device for a circulating tumor cell–based diagnosis of metastatic cancer and a personalized medicine approach regarding the decision of which chemotherapeutic course should be taken.